2016
DOI: 10.1177/1071100716674997
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Direct Ligament Repair and Tenodesis Reconstruction on Simulated Subtalar Joint Instability

Abstract: The Gould modification of Broström ligament repair may be a favorable operative procedure for the restoration of subtalar and ankle joint kinematics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 40 publications
(78 reference statements)
2
27
0
Order By: Relevance
“…This method was also adopted in our numerical analysis. The model was validated by comparing the results of our numerical analysis with previous experimental data [4,13].It was found that the inversion and external rotation of the subtalar joint in the intact/instability model under a torsional moment of 4 Nm were consistent between our simulation and Pellegrini's experiment (Table 4). The inversion under 1.5Nm and the internal rotation under 3Nm of the subtalar joint in our simulation were close to Choisne's results (Table 5).…”
Section: Simulation Of Subtalar Instability and Validationsupporting
confidence: 73%
See 1 more Smart Citation
“…This method was also adopted in our numerical analysis. The model was validated by comparing the results of our numerical analysis with previous experimental data [4,13].It was found that the inversion and external rotation of the subtalar joint in the intact/instability model under a torsional moment of 4 Nm were consistent between our simulation and Pellegrini's experiment (Table 4). The inversion under 1.5Nm and the internal rotation under 3Nm of the subtalar joint in our simulation were close to Choisne's results (Table 5).…”
Section: Simulation Of Subtalar Instability and Validationsupporting
confidence: 73%
“…An FE model of subtalar instability was developed based on one of our previous studies [15]. The subtalar instability was simulated by removing the CFL, ITCL and CL, as suggested by a previous cadaveric study [13]. Due to the fact that subtalar instability rarely occurs alone, the ATFL was also removed before performing the analysis of Schon triligamentous reconstruction and Mann triligamentous reconstruction.…”
Section: Methodsmentioning
confidence: 99%
“…During the foot strike of stair descent, the foot was loaded and excessively plantar‐flexed, predisposing the foot to increased risk of ankle sprain. The calcaneofibular ligament section in cadaveric studies was associated with increased tibiotalar and subtalar inversion; however, with a plantar‐flexed foot, reconstruction of the calcaneofibular ligament could not refrain tibiotalar inversion . When the foot is plantar‐flexed, the anterior talofibular ligament is a more important structure to refrain excessive inversion .…”
Section: Discussionmentioning
confidence: 97%
“…The ligamentous structure is important in subtalar stability. The calcaneofibular ligament is associated with both tibiotalar and subtalar joint inversion/eversion stability . A carefully designed in vitro study reported increased subtalar inversion and external rotation after calcaneofibular ligament sectioning .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation